ANALISIS PENGARUH PENGUNGKAPAN CSR, PERUBAHAN UKURAN PERUSAHAAN, LIKUIDITAS, LEVERAGE, DAN PROFITABILITAS TERHADAP RETURN SAHAM (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar Di Bursa Efek Indonesia Periode 2018-2020) - Amara Sella Pradista; Eny Kusumawati (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Stock returns had a significant impact on investors and companies, stock returns were used as a measure of company performance by investors to invest in companies in the stock market. This study aims to determine the effect of CSR disclosure, company size, liquidity, leverage, and profitability on stock returns in manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2020 period. The sampling technique used in this research was purposive sampling. The sample of this study consisted of a unit analysis of 351 companies that met the criteria. The analytical method used is multiple linear regression analysis. The result of the hypothesis testing indicated that profitability has an effect on stock returns. Meanwhile, CSR disclosure, firm size, liquidity, and leverage have no effect on stock returns